Swearwords in Subtitling: A Case Study on Students’ Translation Project - Raden Arief Nugroho; Rahmanti Asmarani (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2019)
Despite their consideration as impolite remarks in communication, swearwords play an inseparable part from linguistics repertoire. As defined by Aijmer (2002:12), swearwords “[express] the speaker’s attitude towards the situation spoken about, his assumptions, his intentions, his emotions”. Carrying ‘negative’ label makes swearwords the centre of attention. Interestingly, movies that have turned into public entertainment sphere blooms the use of swearwords. The statement is supported by Azzaro (2005:1) who states that “television is often blamed for the circulation of once forbidden expression, and films in particular get the blame.” To add fuel to the fire, Cressman et al (2009) has also noted a rising frequency of swearwords usages in Hollywood movies. With the increasing number of Hollywood movies in Indonesia, English swearwords phenomena cannot be neglected. However, deleting or even softening swearwords will put the artistic touch of cinematography at stake. In this context, translators, especially subtitle translators, play an important role in dealing with swearwords phenomenon. As to introduce translation students to this complex matter, the writer gave them a subtitling task of swearwords. Twenty students consisting of twelve males and eight females were involved in this project and ‘8 Miles’ movie was used as the translation task. Surprisingly, both male and female students did not try to soften or delete the use of swearwords. Most of the English swearwords were adopted into Indonesian swearwords.